Features of blood supply to the human kidney with a five-segment concept of its structure - Vezirkhanov, Abuselim Zagidovich; Kafarov, Edgar Sabirovich; Sysoev, Petr Alexandrovich (Gaceta Médica de Caracas, 2022)
The purpose of the research was a study of sources of blood supply to the segments of the kidney in the most common variant of the branching of the renal artery and its branches. The material for the study was 116 corrosive preparations of the arterial system of the human kidney, made of fast-hardening polymers. These preparations were subsequently subjected to 3D scanning and topographic and anatomical analysis.